Developing and testing a measure of COVID-19 organizational support of healthcare workers – results from Peru, Ecuador, and Bolivia. (September 2020) - Zhang, Stephen X.; Sun, Shuhua; Afshar Jahanshahi, Asghar; Alvarez-Risco, Aldo; Ibarra, Verónica García; Li, Jizhen; Patty-Tito, Ross Mary
Highlights: We devised a brief 8-item measure of COVID-19 organizational support (COVID-OS). The measure has three dimensions: work support, personal support, and risk support. All three dimensions demonstrated criterion validity of predicting anxiety and satisfaction. Work support discriminated healthcare workers with minimal and mild anxiety. Personal support discriminated between people with mild and moderate anxiety. Abstract: During the COVID-19 pandemic, healthcare workers are facing high workloads with resource constraints and risk of virus exposure, and healthcare organizations need to support their healthcare workers to reduce their anxiety. Based on a recent 8-point framework of COVID-19 specific organization support, we devised a measure of COVID-19 Organizational Support (COVID-OS). We tested the new measure with 712 healthcare workers in Bolivia, Ecuador, and Peru and found the new measure formed three factors to predict healthcare workers' anxiety and life satisfaction during the COVID-19 pandemic. We call for further studies to test COVID-OS in other countries and settings.